2017
DOI: 10.1002/esp.4132
|View full text |Cite
|
Sign up to set email alerts
|

Sediment transport in high‐speed flows over a fixed bed: 2. Particle impacts and abrasion prediction

Abstract: Single bed load particle impacts were experimentally investigated in supercritical open channel flow over a fixed planar bed of low relative roughness height simulating high‐gradient non‐alluvial mountain streams as well as hydraulic structures. Particle impact characteristics (impact velocity, impact angle, Stokes number, restitution and dynamic friction coefficients) were determined for a wide range of hydraulic parameters and particle properties. Particle impact velocity scaled with the particle velocity, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
104
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(126 citation statements)
references
References 52 publications
(199 reference statements)
13
104
4
Order By: Relevance
“…3) that includes both tools and cover effects and that is consistent with current process understanding (e.g. Beer et al, 2017;Fuller et al, 2016;Sklar and Dietrich, 2004), as well as quantitative field and laboratory measurements (Auel et al, 2017;Beer and Turowski, 2015;Chatanantavet and Parker, 2009;Inoue et al, 2014;. The model presented here thus improves upon existing 1-D reach-scale models both in the plausibility of the underlying assumptions and, as has been shown in Sect.…”
Section: Comparison To Previous Modelssupporting
confidence: 62%
See 3 more Smart Citations
“…3) that includes both tools and cover effects and that is consistent with current process understanding (e.g. Beer et al, 2017;Fuller et al, 2016;Sklar and Dietrich, 2004), as well as quantitative field and laboratory measurements (Auel et al, 2017;Beer and Turowski, 2015;Chatanantavet and Parker, 2009;Inoue et al, 2014;. The model presented here thus improves upon existing 1-D reach-scale models both in the plausibility of the underlying assumptions and, as has been shown in Sect.…”
Section: Comparison To Previous Modelssupporting
confidence: 62%
“…As before, Q s is the upstream bedload sediment supply. Note that in the original saltation-abrasion model (Sklar and Dietrich, 2004), k depends explicitly on hydraulics, but, consistently, in all of the field and laboratory studies where all relevant parameters have been measured, this dependency has not been found (Auel et al, 2017;Beer and Turowski, 2015;Chatanantavet and Parker, 2009;Inoue et al, 2014;. At steady state, C = C c .…”
Section: Lateral Erosion and Bedrock Channel Widthmentioning
confidence: 94%
See 2 more Smart Citations
“…The present study analyses particle transport modes, velocities, hop lengths and hop heights. Particle impact velocities and impact angles, Stokes number, restitution and dynamic friction coefficients and their application for an abrasion prediction model are separately covered in an accompanying paper (Auel et al 2017).…”
Section: Abrasionmentioning
confidence: 99%